2001
DOI: 10.1038/modpathol.3880322
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Chromosome 16q Loss Differs between an Atypical Proliferative Lesion and an Intraductal or Invasive Ductal Carcinoma Occurring Subsequently in the Same Area of the Breast

Abstract: Atypical proliferative lesions of the breast, such as atypical ductal hyperplasia and atypical papilloma, are considered to be precursors of breast carcinomas and have frequently been shown to have loss of heterozygosity (LOH) on chromosome 16q at the DNA level. We evaluated whether an atypical proliferative lesion and a carcinoma that subsequently occurred in the same area of the ipsilateral breast were of identical clonal origin in seven patients. Using DNA isolated from microdissected archival tissue of epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Atypical ductal hyperplasia (ADH), defined by Page, is very similar to cribriform-type DCIS in its histological features, but its size is 2.0 mm or less, and the degree of structural atypia is a little weaker than in cribriform type DCIS. Although ADH is generally considered to be a precancerous condition, LOH on 16q is already detectable [88,89].…”
Section: E-cadherin Gene Mutationsmentioning
confidence: 99%
“…Atypical ductal hyperplasia (ADH), defined by Page, is very similar to cribriform-type DCIS in its histological features, but its size is 2.0 mm or less, and the degree of structural atypia is a little weaker than in cribriform type DCIS. Although ADH is generally considered to be a precancerous condition, LOH on 16q is already detectable [88,89].…”
Section: E-cadherin Gene Mutationsmentioning
confidence: 99%
“…Loss of 16q and gain of 1q are well documented as features of the low-grade family of breast carcinomas, including flat epithelial atypia; lobular neoplasia; lowgrade DCIS; and invasive lobular, tubular, cribriform and low-grade ductal carcinomas [1][2][3][4][8][9][10]46,139,[164][165][166]. Although gain of 1q is one of the most frequent genomic changes in breast cancer and has been extensively studied, the mechanisms leading to this genomic aberration are still poorly characterized.…”
Section: Der16 T(1;16)(p10;q10)mentioning
confidence: 99%
“…Tsuda et al (7,8) reported that papillary carcinomas have frequent changes in gene copynumber and loss of heterozygosity (LOH), while papillomas did not show any gene copy-number alteration or LOH at 16q and 1q. Boecker et al (9) also reported that conventional comparative genomic hybridization (CGH) did not reveal any gene copynumber change in papillomas.…”
Section: Introductionmentioning
confidence: 99%